2008
DOI: 10.1590/s1413-35552008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de dois procedimentos educacionais sobre os sintomas musculoesqueléticos em trabalhadores administrativos

Abstract: Objective: To investigate the effect of applying two educational programs (one using a self-instructional approach and the other using a traditional approach similar to educational workshops), on the perceived frequency of musculoskeletal symptoms. Methods: A quasiexperimental study was conducted in 94 office workers in a public company. The participants were divided into three groups through simple randomized sampling with no replacement. The first group (32 employees) underwent a traditional/workshop program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
3
0
6
Order By: Relevance
“…Other studies conducted with office workers found that workers reported the neck (20,32) and shoulders (20) most frequently. De Vitta et al (15) found that raising awareness among employees regarding the adoption of new postures and the organization of the work environment resulted in reduced frequency of musculoskeletal symptoms. Analysis of the outsourced staff in the present study demonstrated that the most affected sites were the lower back, shoulder and hips/lower limbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies conducted with office workers found that workers reported the neck (20,32) and shoulders (20) most frequently. De Vitta et al (15) found that raising awareness among employees regarding the adoption of new postures and the organization of the work environment resulted in reduced frequency of musculoskeletal symptoms. Analysis of the outsourced staff in the present study demonstrated that the most affected sites were the lower back, shoulder and hips/lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…A WMSD diagnosis is complicated and frequently delayed, as it is based only on patient complaints, which cannot always be verified (13,14). This characteristic makes treatment difficult and strongly influences the conduct of workers in and out of the work environment (1,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Para o Estado, um alto gasto com pagamentos de benefícios previdenciários, tratamento e reabilitação. Para a empresa, perda na produção e na qualidade no serviço pela diminuição do número de funcionários e horas de trabalho; e para o indivíduo, sofrimento, incapacidade para o trabalho, para a atividade do cotidiano e vida social (13) .…”
Section: Introductionunclassified
“…Com intuito de obter dados relevantes sobre as condições de trabalho, foi entregue um questionário multidimensional, adaptado para o presente estudo, que continha questões sobre cargo que ocupa, posição adotada durante a tarefa que desempenha, realização de atividades extralaborais e prática de atividade física(16) . Além disso, vale ressaltar que, para facilitar a localização dolorosa, foi apresentada uma figura ilustrativa do corpo humano(17) .Para apresentação dos dados, foi utilizada estatística descritiva, com os dados sendo repre sentados com valores de média, desvio padrão, percentuais e números absolutos, com o auxílio do programa SPSS, versão13.0. O estudo foi iniciado após aprovação pelo Comitê de Ética em Pesquisa envolvendo Seres Humanos, da Universidade Comunitária da Região de Chapecó, com o protocolo nº 355/12, atendendo aos requisitos da Resolução 466/12 e suas complementares do Conselho Nacional de Saúde, e autorização da empresa onde foi realizado o estudo.…”
unclassified
“…A suitable design of computerized workstations may contribute to the reduction of occupational diseases and ergonomic hazards, and increase workers' comfort at work (1,3,4).…”
Section: Introductionmentioning
confidence: 99%